Climate change 2007 : impacts, adaptation and vulnerability : contribution of Working Group II to the fourth assessment report of the Intergovernmental Panel on Climate Change - Parry, M. L. (Martin L.) (Cambridge, U.K. Cambridge University Press, 2008)
40